Comparative analysis of cyclotide-producing plant cell suspensions presents opportunities for cyclotide plant molecular farming. (March 2022) - Doffek, Benjamin; Huang, Yvonne; Huang, Yen-Hua; Chan, Lai Yue; Gilding, Edward K.; Jackson, Mark A.; Craik, David J.
Abstract: Cyclotides are a class of ribosomally-synthesized plant peptides that function in plants as a defense against insects and fungal pathogens. Their unique structure comprises a cyclized peptide backbone threaded by three disulfide bonds, that imparts structural stability, a desirable quality for peptide-based therapeutics or insecticides. Producing these peptides synthetically is challenging due to the amount of chemical waste produced and inefficiency of folding certain cyclotides. Thus, it is desirable to develop a means to access cyclotide biosynthesis in their native hosts, cultured in defined conditions, at both laboratory and commercial scale. Here we developed suspension cell cultures from two species previously unexplored for cyclotide production in suspension cells, Clitoria ternatea L., Hybanthus enneaspermus F. Muell., as well as with Oldenlandia affinis (Roem. & Schult.) DC., a species reported previously to accumulate cyclotides in cell suspensions. We assessed the growth rate, cyclotide production and gene expression for the various species. We found that while many cyclotides had reduced expression in Oldenlandia affinis suspension cells when compared to plant organs, those in Clitoria ternatea and Hybanthus enneaspermus maintained or increased expression levels. The cyclotides that continued to be expressed in suspension cultures shared similar sequence and biophysical properties as a group, regardless of phylogenetic origin of the host. Of particular interest was the discovery of inducibility by NaCl of cyclotide expression in O. affinis, cycloviolacin O2 expression in O. affinis, and the scale up of cycloviolacin O2 production in H. enneaspermus . Together the results presented here highlight the utility of plant cell suspensions as modalities to produce macrocyclic peptides. Graphical abstract: Image 1 Highlights: Cyclotides from suspension cells differ in diversity compared to those produced in plant organs. Biosynthetic AEP expression is maintained in suspension cells. Cross family conservation of the potent insecticidal cyclotide cyO2. Production of cyO2 at scale using a rocking motion bioreactor.